Virtual Classrooms and Digital Learning: An Analysis of Metaverse in Education - Nur Albar, Chepi (International Journal of Research and Applied Technology (INJURATECH), 2023)
The integration of the metaverse into education has the potential to revolutionize digital learning by creating immersive, interactive, and highly engaging virtual classrooms. This study examines how metaverse technologies enhance digital learning experiences, identifying both the opportunities and challenges they present. The research utilizes a mixed-method approach, combining surveys and interviews with educators and students to assess the effectiveness of metaverse-based learning. Findings suggest that while the metaverse fosters greater student engagement and collaboration, issues such as accessibility, high implementation costs, and ethical concerns must be addressed. This study contributes to the growing discourse on the future of education in a digital age, offering insights for educators, policymakers, and technology developers